?-Tocopherol and Ketorolac on Pain in Long Evans Rats - Rouf, Mahadi Abdur; Begum, Shelina; Ali, Taskina; Rahman, Md Mizanur; Masood, Shahriar (Journal of Bangladesh Society of Physiologist, 2017)
Background: Alpha-tocopherol (áT) is a form of vitamin E that is widely known to be one of the reactive oxygen species scavengers (ROS) and it has been shown to have analgesic effects in different animal and human studies. But comparison of these effects with similar effects of ketorolac tromethamine (KT) and their combination have not been established. Objective: To assess the effects of ?T on pain and also compare them with those of the combinations of ?T with KT in rat models Methods: This experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2015 to February 2016. For this, 20 (twenty) Long Evans rats (215±35 gm) of both sexes were divided into control (A, with 5mL/kg normal saline) and experimental (B1, with 500mg/kg ?T; B2, with 10mg/kg KT; B3, with ?T +KT) groups with 5 (five) rats in each group. All the drugs and vitamins were administered intraperitoneally in a single dose, just one hour before formalin test.To evaluate the effect of treatments on nociceptive pain, early phase (1st - 5th minutes); on central analgesic system, interphase (6th - 15th minutes); and on inflammatory pain, late phase (16th-60th minutes) of the formalin test, were observed. In all phases, total frequency of jerking and total duration of flexing and licking of the right hind paw were counted after administration of subcutaneous formalin (50 ?L, 2.5%) injection. Statistical analysis was done by ANOVA, followed by Bonferroni post hoc test. In the interpretation of results, p?0.05 was considered as significant. Results: ?T lowered flexing and licking duration significantly (p?0.001) in early and late phases. KT lowered flexing and licking duration significantly (P<0.001) in late phase of formalin test. On the other hand, combination of ?T and KT significantly (p?0.001) lowered both the study variables in early and late phase of formalin test. Conclusion: From this study it may be concluded that, ?T possesses analgesic effects and combination of ?T with KT is more effective than those of their individual administration. Bangladesh Soc Physiol. 2017, June; 12(1): 21-27